Kapok oil methyl esters - Rashid, Umer; Knothe, Gerhard; Yunus, Robiah; Evangelista, Roque L. (Pergamon Press, 2014)
The increased need for biodiesel feedstocks has caused various vegetable oils to be examined for this purpose. In the present work, the methyl esters of kapok (Ceiba pentandra) oil were prepared. The essential fuel properties were comprehensively determined and evaluated in comparison to specifications in biodiesel standards and some prior results. The kinematic viscosity of kapok oil methyl esters was greater than expected, an observation traced to the elevated amounts of methyl esters with cyclic moieties. Overall, kapok oil is a potential biodiesel feedstock. The 1H and 13C NMR spectra of kapok methyl esters are reported.